THE INFLUENCE OF VOCATIONAL PROGRAMS AT AL-AZHAR MEDAN SENIOR HIGH SCHOOL ON THE RELEVANCE OF STUDENTS’ UNIVERSITY STUDY CHOICES - Fachry Akbar Buandra; M Farhan Al Ghifahri Pane; Ahmad Rafi Akbar Silalahi; Ziyad Zaky (PT. Radja Intercontinental Publishing, 2025)
This study was conducted to analyze the extent to which the implementation of vocational programs at Al-Azhar Medan Senior High School influences the relevance of students’ study program selections at the university level. A quantitative approach was employed by utilizing data from alumni who had continued their education to higher institutions. The analysis results indicate that the majority of students chose university majors that align with their high school vocational fields, although some opted for different areas. Factors such as individual interests, counseling services, and family involvement also contributed to the academic decision-making process. These findings highlight the importance of school support in guiding students to determine their academic paths appropriately from the high school level to ensure continuity and coherence in their educational progression.